Problems affecting squatter settlements in Nampula, Mozambique - Hamza Momade, Mohammed; Mohd Rosli Hainin, Prof (International Journal of Engineering and Technology, 2018)
The global challenge to eradicate squatter settlements locally known as â€œrent free havensâ€ in cities of Mozambique has been a challenging issue since the country gained independence. Successive governments after independence have not been able to adequately deal with the squatter problems. This study is carried out in the squatter district of Nampula, Mozambique. The data is analyzed using SPSS and Average Index. From the study the factors are identified and prioritized for improvement of squatter settlements needed in each case. There is no proper infrastructure such as paved roads, footpath, or sidewalk in place at the moment. The drainage system is very poor and during raining season results in heavy floods which destroy almost all squatter residents which is why theyâ€™re rebuilt every year. The squatter residents built the houses by themselves, which is why there was a poor construction practice. The steps to be taken by the authorities to overcome the squatter issues are meeting the residents of the squatter areas and provide information and make them aware regarding the conditions of their respective areas through the studies that has been carried out, provide the options available like short term loan, rural investment, self-help schemes and self-involvement in Design and Construction.